Targeted and Non-Targeted Analysis of Endocrine Disruptors in the Urine of Female Personal Care Professionals - Martinez, Vanessa (Université d'Ottawa / University of Ottawa, 2025)
Endocrine-disrupting chemicals (EDCs) refer primarily to synthetic chemicals that specifically disrupt the functions of the endocrine system, resulting in an increased risk for reproductive, developmental, and transgenerational health issues. EDCs are commonly added to a range of consumer products, including personal care products. Personal care professionals, like hairdressers and aestheticians, are exposed daily to various EDCs through their direct occupational use of personal care products. Female personal care professionals may have an elevated EDC exposure due to their occupational and personal use of such products. This thesis reports on the development of a targeted (TA) and non-targeted analysis (NTA) workflow that can screen a wide range of known and unknown urinary metabolites of EDCs in female personal care professionals. This workflow was developed using liquid chromatography-mass spectrometry (LC-MS) and covered six groups of EDCs: antimicrobials, benzophenones, bisphenols, parabens, phthalates, and perfluoroalkyl substances (PFAS). This study recruited the urine of 32 participants from different regions of Québec, including 14 female personal care professionals and 18 females from unrelated occupations. The results demonstrated an elevated concentration of benzophenones, parabens, monophthalates, and bisphenols in the exposed group compared to the control group. NTA revealed eight additional chemicals that are known EDCs or not previously reported. Overall, these findings demonstrate that personal care professionals have a higher average EDC exposure compared to unrelated occupations. This highlights the concerns of personal care product use in personal care professionals and potential consideration for further regulatory decisions regarding their use. Most importantly, this study informs female personal care professionals of their elevated exposure so they may make more informed decisions regarding their personal care product use at work and at home.
Keywords: Non-targeted analysis; Endocrine Disruptors; Urine Analysis